The children's nursing workforce in Kenya, Malawi, Uganda, South Africa and Zambia: generating an initial indication of the extent of the workforce and training activity - Natasha North; Maylene Shung-King; Minette Coetzee (BMC, 2019)
Abstract Background This study sought to identify, as far as possible, the extent of the specialist children's nursing workforce in five selected African countries. Strengthening children's nursing training has been recommended as a primary strategy to reduce the under-five mortality rate in African nations. However, information about the extent of the specialist children's nursing workforce in this region is not routinely available. Developing an accurate depiction of the specialist children's nursing workforce is a necessary step towards optimising children's health service delivery. Methods This study used a convergent parallel mixed methods design, incorporating quantitative (surveys) and qualitative (questionnaire and interview) components, to generate data addressing three related questions: how many children's nurses are believed to be in practice nationally, how many such nurses are recorded on the national nursing register and how many children's nurses are being produced through training annually. Results Data provide insights into reported children's nursing workforce capacity, training activity and national training output in the five countries. Findings suggest there are approximately 3728 children's nurses across the five countries in this study, with the majority in South Africa. A total of 16 educational programmes leading to a qualification in paediatric nursing or child health nursing are offered by 10 institutions across the countries in this study, with Kenya, Malawi and Zambia having one institution each and South Africa hosting seven. Data suggest that existing human resources for health information systems do not currently produce adequate information regarding the children's nursing workforce. Analysis of qualitative data elicited two themes: the role of children's nurses and their position within health systems, and the capacity of HRH information systems to accurately reflect the specialist children's nursing workforce. Conclusion The data generated provide an initial indication of the size of the children's nursing workforce in these five countries, as well as an overview of associated training activity. We hope that they can start to inform discussion about what would represent a viable and sustainable regional children's nursing workforce for the future.